تطوير الأداء الإداري للهيئة العامة لتعليم الكبار بمصر - محمد، دولت حامد Mohammed, Dawlat Hamed; عباس، آمال العرباوي مهدي Abbas, Amal Alarabawi Mahdi; سليمان، حنان حسن (جامعة قناة السويس - كلية التربية بالإسماعيلية, 2022)
هدفت الدراسة إلي تطوير الأداء الإداري للهيئة العامة لتعليم الكبار بمصر، وفي سبيل ذلك استخدمت الباحثة المنهج المختلط بشقيه الكمي والكيفي، مستخدمة المقابلة الشخصية وبطاقة الملاحظة والاستبانة كأدوات لجمع البيانات؛ وقامت الدراسة من خلال الإطار النظري باستعراض الأسس الفلسفية للأداء الإداري بالمؤسسات التعليمية من خلال عرض مفهوم الأداء الإداري، وكيفيه تطوير الأداء الإداري بالمؤسسات التعليمية، واستراتيجيات تطوير الأداء الإداري بالمؤسسات التعليمية، ثم توصلت من خلال الدراسة الميدانية إلي الصعوبات التي تواجه إدارة الهيئة العامة لتعليم الكبار في تطوير أدائها والتي تمثلت في التمويل، صعوبات مرتبطة بالعمل، صعوبات مرتبطة بالعاملين، صعوبات خاصة ببيئة العمل، صعوبات خاصة بأوضاع ونظم تقنيات المعلومات، ومن ثم وضع تصور مقترح لتطوير الأداء الإداري للهيئة العامة لتعليم الكبار للتغلب على تلك الصعوبات تمثل في ستة محاور وهي تحسين مهارات وسلوك العاملين، التطوير التنظيمي وإعادة الهيكلة، تحسين العمليات الإدارية، تحسين البنية التحتية المادية، التطوير التقني، إتاحة البيانات. The study aimed at developing the performance of the General Authority for Adult Education in Egypt, The researcher used mixed approaches by quantity and qualitative sides, Personal interviewer, Observation card and Questionnaire as data collection tools. Through the theoretical framework researcher reviewed the intellectual framework of administrative performance, as well as the concept, how to develop the administrative performance in educational organizations, and the developing the performance strategies, The study ended with the application to difficulties facing the general authority for adult education to developing the performance, were financial difficulties, work-related difficulties, difficulties associated with employees, work environment difficulties, difficulties related to the status and systems of information technology, and then a proposed scenario for developing the performance of the General Authority for adult Education in Egypt in six axes, improve the skills an behavior of employees, organizational development and restructuring, improving administrative processes, improve physical infrastructure, technical development, data availability.
Keywords: الأداء الإداري -- المؤسسات التعليمية -- تعليم الكبار -- التطوير التنظيمي -- مصر